ANALISIS KESALAHAN HANGEUL MATCHUMBOEP (EJAAN BAHASA KOREA) DALAM PENULISAN ESAI DESKRIPTIF MAHASISWA PENDIDIKAN BAHASA KOREA ANGKATAN 2017 [ERROR ANALYSIS OF HANGEUL MATCHUMBOEP (KOREAN SPELLING) ON CLASS 2017 KOREAN LANGUAGE EDUCATION STUDENTS’ DESCRIPTIVE ESSAYS] - Raden Sarah Muflihah; Renariah Renariah; Risa Triarisanti (Metalingua: Jurnal Penelitian Bahasa, 2021)
This research is a descriptive qualitative study that aims to analyze the errors of Hangeul Matchumboep (Korean Spelling) in descriptive essays of Korean language education students. The focus of this research is to describe the types of Korean spelling errors and to calculate the percentage of Korean spelling errors made by students of Korean Language Study Program at the Faculty of Language and Literature of the Indonesian University of Education class of 2017. The data of this research are descriptive essays written by Korean language education students class of 2017. As for the selection of the participants, the researcher employs a simple random sampling technique with a total of 38 participants, which then divided into three types; high, medium, and low error values. The results indicate that the higher the value, the lower the error rate. Types of dominant writing errors are the type of vocal letter substitution error with 43,24% and the use of spaces with 45,94%. After the types of spelling mistakes were found, it can be concluded that the cause of these errors is the lack of student competence in understanding the use of vocabulary in certain forms of sentences that are bound by the phonological rules. This effect can be caused by learning incomplete second language rules learned by students (intralingual) and the influence of language rules from the first language on the second language (interlingual). Keywords: Spelling Error Analysis, Hangeul Matchumboep, Essay